The study of glial scar formation after brain ischemia using in-vitro strategies - Mannava, Raja Sekhar (2015)
Reactive gliosis is a generic response to Central Nervous System (CNS) injury mediated by astrocytes and microglia. Following ischemic damage to the CNS parenchyma, the injured area becomes surrounded by a dense astroglial cell layer known as glial scar. Glial scar formation has been recognized for many decades as a major impediment for neuronal reconnection and a serious obstacle for functional recovery. However, more recent studies have shown that scar limits the area of damage, preventing the diffusion of blood-derived activated immune cells into the CNS that could cause a generalized proinflammatory-neurodegenerative response.\nIn spite that it has been morphologically recognized for many years since Ramon y Cajal times, to study the biochemical signaling cascades involved in glial scar formation has been difficult mostly because of the in vivo nature of the process.\nIn this context, we studied here the mechanisms of glial scar assembly/disassembly in vitro to identify potential pharmacological targets for therapeutic interventions. To achieve this goal we will use the classical 2-Dimensional (2D) astroglial cultures, but we will also develop 3-dimensional (3D) astroglial cultures by using nanotube matrixes to attempt to better reproduce the in vivo situation. The results of this thesis showed that meningeal macrophages or ischemia-activated macrophages induce astroglial retraction and formation of scar-like structures in vitro. Scar-forming astrocytes over-express GFAP, S100B and TLR2-4. Using the NF-?B antagonist BAY-11-7082 we demonstrated that scar formation and its density is partially NF-?B dependent. Finally, in 3D astroglial culture grown on hydromatrix nanotubes, we showed that DAMPs can induce astroglial polarization but not the formation of the glial scar in vitro. We conclude that TLR/ NF-?B pathway is probably implicated in the glial scar formation or stabilization and that DAMPs and macrophages are necessary for the formation of glial scars in vitro.